Tupá poranĕní ledvin--vlastní zkusenosti a soucasné názory na jejich lécbu - Base, J; Navrátilová, J; Zborilová, I; Urbanová, E (Sbornik vedeckych praci Lekarske fakulty Karlovy univerzity v Hradci Kralove. Supplementum, 1995)
Between 1972 to 1994 there were admitted 105 patients with blunt trauma of the kidney, 89 men and 16 women with median age 32 years. In 53 patients the left kidney was affected and in 52 of them the right side was injured. According to the grade of trauma we evaluated in 77 patients a contusion (73.3%), by 16 patients a laceration (15.2%), in 11 patients a rupture of the kidney with fragmentation of the parenchyma and in one the renal artery was injured. The mechanism leading to the blunt trauma of the kidney was following: traffic accident in 52 patients (49.5%), during sport in 20 patients (19.5%). 16 patients were injured in own home (9.5%) and 7 patients in work (6.7%). In 28 patients the trauma of the kidney was serious, by 5 of them we have done nephrectomy (17.8%), in two suture of the parenchyma (7.1%) and in further two patients heminephrectomy. After considering clinical status, grade of hypovolemic shock and finding on CT scan we prefer lately conservative steps in the treatment serious trauma of the kidney.
Keywords: Wounds, Nonpenetrating; ledviny; Female; Adult; dospělí; Kidney; Humans; ženské pohlaví; tupá poranění; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Radiography; Adolescent; mladiství; radiografie